Laboratory Inventory Management Engine (LIME): A free tool for managing laboratory inventories via barcode scanning and automatic cloud-based spreadsheet integration - Tiffany M. Salinas; Leo Tornes; Christopher Solís (PLoS ONE, 2026)
Efficient inventory management remains a persistent challenge in research settings, where productivity and budget control are tightly linked to accurate tracking of consumables, reagents, and equipment for decision-making and successful research project execution. Many laboratories still rely on traditional methods, including handwritten logs or static spreadsheets, which are prone to human error and can result in stockouts, over-ordering, and inaccurate forecasting. Moreover, existing inventory systems often fall short in balancing affordability, convenience, and functionality. Here, the Laboratory Inventory Management Engine (LIME) is introduced as a system designed to bridge these deficiencies by leveraging accessible tools like in-the-cloud spreadsheet files and mobile devices. LIME uses a smartphone app to enable real time updates to the inventory log by scanning consumables QR codes and barcodes. The system allows inputting new items to be classified in predetermined catalog lists (e.g., 4º fridge, chemicals, antibodies, etc.). This dual smartphone and spreadsheet inventory prototype is anticipated to improve the operational efficiency of small academic research laboratories and early-stage startups to benefit their bottom lines.